Transportation conditions of calves upon arrival at major livestock auction markets in Québec, Canada - Marianne Villettaz Robichaud; Marie-Pascale Morin; Gilles Fecteau; Sébastien Buczinski (JDS Communications)
The objective of this cross-sectional observational study was to describe the transport conditions of calves at the time of their arrival at the 2 major livestock auction markets in the province of Québec, Canada, and to identify characteristics that affect bedding cleanliness. A particular emphasis was placed on the transport environment of young dairy calves commonly being marketed for veal production. During 4 d per auction site (n = 2 sites), 2 d in summer and 2 d in winter, the descriptive characteristics including type of transports, number of calves per transport, separation from other transported animals, as well as presence of ventilation sources (e.g., open holes allowing natural ventilation), bedding, and bedding cleanliness, were determined. A total of 507 different transports were included, representing a total of 4,054 calves sold during these 8 d. The vast majority of calves (95% [n = 3,845]) were transported by commercially designed trailers (long commercial trailers (n = 358; 70.6% of all transport types), short commercial trailers (n = 62; 12.2%), or multideck trailers (n = 15; 3%). A minority of calves (5%) were either transported by homemade trailers (n = 30; 5.9% of transport) or other types of transports (n = 42; 8.3%). The presence of any ventilation source in the calves' transportation area was observed in 86% of transports and increased in summer versus winter (odds ratio: 2.75 [95% CI: 1.58–4.79]). Bedding was present in 96% of evaluated transports. The majority (68%) of calves' transport flooring area was considered clean, with less than 33% of the calves' area soiled with manure. The dirtiness of calves' transport flooring area was lower in winter than in summer (odds ratio = 0.63 [0.43–0.92]) and in site B than in site A (odds ratio = 0.57 [0.38–0.94]). This study gives interesting insight into transportation and unloading conditions of surplus calves in commercial auction markets.